Exploring the role of interpersonal contexts in peer relationships among autistic and non-autistic youth in integrated education - Chen, Yu-Lun; Schneider, Maxwell; Patten, Kristie (Frontiers in Psychology, 2022)
The double empathy problem theory posits that autistic social difficulties emerge from an interpersonal misalignment in social experiences and expectations between autistic and non-autistic people. Supporting this, emerging research reveals better social outcomes in interactions within than across neurotypes among autistic and non-autistic people, emphasizing the need to examine the role of the interpersonal context in autistic social outcomes. However, research on peer relationships among autistic youth primarily focuses on individual characteristics in isolation from the interpersonal context. To address this, this preliminary study explored the effects of student-peer neurotype match on peer relationships among autistic and non-autistic youth in an integrated educational setting. We plotted the peer relationship networks among youth in a school club based on systematic observations of peer interactions over eight 45-minute sessions. Descriptive network statistics (node degree and strength) showed that both autistic and non-autistic youth had more and stronger peer relationships with their same- than cross-neurotype peers. Assortativity coefficients revealed a tendency for youth to connect with peers of the same neurotype, rather than with peers with similar social popularity or activity. We further modeled the effects of student-peer neurotype match on peer relationships using exponential random graph models. The findings suggested that student-peer neurotype match predicted the total strength of peer relationships above and beyond the effects of student neurotype, individual heterogeneity in social popularity and activity, and the tendency of mutuality in social relationships. We discussed the strengths and limitations of this study and the implications for future research and inclusion practice.